Smart School Sebagai Solusi Transformasi Digital Pendidikan: Studi Kasus Implementasi Di Sekolah Swasta Indonesia - Hidayanti, Linna; Safuan , Safuan (Jurnal Pendidikan Indonesia, 2025)
Digital transformation has occurred across various fields, as evidenced by the significant market share held by technology companies such as Apple and Microsoft. This also marks the development of educational institutions that have transformed, from the pre-digital era to School 4.0, facilitated by the presence of IoT, data-driven approaches, and the implementation of smart devices. The purpose of this study is to determine the digital transformation implemented by the Bakti Mulya 400 school through Smart School technology. The method used in this study uses qualitative methods with a case study approach. The results of the study show that the implementation of Smart School carried out by Bakti Mulya school can integrate all aspects of the school, including learning, management of school facilities, and infrastructure, to facilitate teaching and learning activities. By combining various interconnected modules, this system not only responds to the needs of the digital era, but also creates an efficient, transparent, and adaptive educational ecosystem for the development of the times. Every aspect of school activities has been digitized through modules that are functionally designed and oriented towards centralized services.